Phonetics or phonology: asymmetries in loanword adaptations; French and German mid front rounded vowels in Japanese - Dohlus, Katrin (ZAS Papers in Linguistics, 2005)
It is one of the most highly debated issues in loanword phonology whether loanword adaptations are phonologically or phonetically driven. This paper addresses this issue and aims at demonstrating that only the acceptance of both a phonological as well as a phonetic approximation stance can adequately account for the data found in Japanese. This point will be exemplified with the adaptation of German and French mid front rounded vowels in Japanese. It will be argued that the adaptation of German /oe/ and /ø/ as Japanese /e/ is phonologically grounded, whereas the adaptation of French /oe/ and /ø/ as Japanese /u/ is phonetically grounded. This asymmetry in the adaptation process of German and French mid front rounded vowels and further examples of loans in Japanese lead to the only conclusion that both strategies of loanword adaptation occur in languages. It will be shown that not only perception, but also the influence of orthography, of conventions and the knowledge of the source language play a role in the adaptation process.